Pseudothrombocytopenia Due to Platelet Clumping: A Case Report of Prolonged Hospitalization Due to Confounded Diagnosis - Gede Made Cahya Trisna Pratama; I Komang Wisuda Dwija Putra (Jurnal Impresi Indonesia, 2026)
Platelets are pivotal for hemostasis, and accurate quantification is essential for clinical decision-making. Pseudothrombocytopenia (PTCP) is a spurious laboratory finding characterized by falsely low platelet counts due to in vitro clumping, most commonly induced by the ethylenediaminetetraacetic acid (EDTA) anticoagulant. This phenomenon can lead to significant diagnostic confusion and unnecessary medical interventions. This case report describes a 47-year-old female presenting with abdominal pain and vomiting, initially diagnosed with gastritis. Despite clinical improvement, persistent thrombocytopenia raised concerns for conditions such as dengue hemorrhagic fever or immune thrombocytopenic purpura, prolonging hospitalization. A peripheral blood smear eventually revealed platelet clumping, confirming PTCP. This case underscores that PTCP is a preanalytical artifact which, if unrecognized, can result in diagnostic errors, overtreatment, and increased healthcare costs. Clinicians and laboratory personnel must consider PTCP in the differential diagnosis of unexplained thrombocytopenia, especially in asymptomatic patients. Utilizing alternative anticoagulants (e.g., citrate) or examining a peripheral blood smear are critical steps to prevent mismanagement.